2016
DOI: 10.2147/ppa.s104891
|View full text |Cite
|
Sign up to set email alerts
|

Patient attitudes and understanding about biosimilars: an international cross-sectional survey

Abstract: ObjectiveTo understand the levels of awareness, usage, and knowledge of biosimilars among patients, caregivers, and the general population in the US and the European Union; perceptions of biosimilars compared to originator biologics; perceived benefits and drawbacks of clinical trials; and whether advocacy groups impact patients’ willingness to try a biosimilar.MethodsAn international survey was conducted which contained up to 56 closed-ended (requiring yes/no or ranking answers) and open-ended questions, depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 10 publications
(11 reference statements)
5
64
0
1
Order By: Relevance
“…The proportion of our cohort who was familiar with biosimilar therapy was very low; this result matched the 9–11% biosimilar awareness levels among patients with inflammatory conditions in the United States and Europe . This low level of awareness was reported despite an Australian Government initiative to raise biosimilar awareness in 2015.…”
Section: Discussionsupporting
confidence: 57%
“…The proportion of our cohort who was familiar with biosimilar therapy was very low; this result matched the 9–11% biosimilar awareness levels among patients with inflammatory conditions in the United States and Europe . This low level of awareness was reported despite an Australian Government initiative to raise biosimilar awareness in 2015.…”
Section: Discussionsupporting
confidence: 57%
“…One publication reported that in Europe and the USA showing only 6% of the general population have even a general impression of biosimilars, although significantly higher awareness (20%–30%) exists in patients diagnosed with a disease for which one or more biologic therapy is available and who are members of a patient advocacy group [17]. …”
Section: Introductionmentioning
confidence: 99%
“…Patients must trust that prescribed drugs are reliable and safe, and were produced according to high quality standards. Studies exploring patients’ attitudes toward biosimilars have identified issues such as a low awareness of these treatments, a desire to be involved in treatment decisions, and the belief that cost savings should not be prioritized above efficacy and safety . Therefore, there exists an immediate need for effective patient education on biosimilars.…”
Section: Health Care Professional and Patient Perceptions: Trust And mentioning
confidence: 99%
“…Combined with a need for education about biosimilars , such discrepancies may be confusing or worrying for health care professionals, patients, and other stakeholders, and could contribute to reduced confidence in the quality, efficacy, and reliability of these biological agents. Moreover, manufacturers must balance the need to account for regulatory variations against the costs of the studies required to seek biosimilar approvals in all geographic regions .…”
Section: Introductionmentioning
confidence: 99%